If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + x = 3x Solving 13 + x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 13 + x + -3x = 3x + -3x Combine like terms: x + -3x = -2x 13 + -2x = 3x + -3x Combine like terms: 3x + -3x = 0 13 + -2x = 0 Add '-13' to each side of the equation. 13 + -13 + -2x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 0 + -13 -2x = 0 + -13 Combine like terms: 0 + -13 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 6+9=-3-27 | | .0583= | | 11+16=-3(6x-9) | | -7+6(-8n+8)=(2n+5)+7 | | 5x-7+2x=9x+3-10 | | (-6m-9)+(3m+18)= | | -78+12x=22+8x | | (x^3)=7x | | 60x^2-75x=0 | | -2(2x+7)-7(8x-6)=-76 | | -3(2x-7)+2(5x+4)-10=11 | | 1/2x^5 | | 3x+50=3x-50 | | y=x^4-12x^3+35x^2 | | -5w-33=-2(w+9) | | -72+9x=80+x | | 60x^2-75=0 | | 3/x=6/x-4 | | 45x+12=244x+234 | | 11+-77+6=30 | | 7(3x+4)-8(2x+5)=13 | | 0.2x^2-6x+50=250 | | 4T-8=-16 | | x+8=6x+23 | | X(5)=60 | | 3/7x-8/9 | | 0.2x^2-6x+60=250 | | tan^2x+4secx+5=0 | | X[5]=60 | | -8=36-5q | | 9x+3x-10=2x+9 | | 3/2(x-9/2)=12 |